Comparative nutritional value and antimicrobial activities between three Euphorbia species growing in Saudi Arabia - Amani S. Awaad; Monerah R. Alothman; Yara M. Zain; Ghada M. Zain; Saleh I. Alqasoumi; Dina A. Hassan (Elsevier, 2017)
Plants are excellent sources of nutrition and highly bioactive substances that might use in the development of new drugs and pharmaceutical agents. Three species of the Genus Euphorbia (Family Euphorpiaceae), namely; Euphorbia granulata Forssk, Euphorbia helioscobia L., and Euphorbia hirta Linn growing in Ryiadh, KSA were air-dried, powdered, and their active materials were extracted with alcohol. The nutritional value phytochemical constituents and antimicrobial activity of the plants were determined. The chemical contents were similar in the three species; however, lipid profile of the plants showed that the stearic acid and lignoceric acid were detected only in E. helioscopia and E. hirta, while palmitoleic acid was detected only in E. hirta. The percentage of unsaturated fatty acid methyl esters were 52.48%, 69.39% and 66.52% in Euphorbia granulate, Euphorbia helioscobia, E. hirta, respectively. Three compounds, 1-ethoxypentacosane, heptacosan-1-ol and β-sitosterol were isolated from the three plant extracts and identified using different spectroscopic analysis. The percentage of crude protein was 43.65%, 25.00% and 18.75% in E. granulata, E. helioscobia, and E. hirta, respectively. The free amino acids and amino acid composition were quantitatively determined using amino acid analyzer. All the plant extracts were active against bacterial and fungal test organisms, however, the antimicrobial activity were varied according to both the Euphorbia species and the test organism. Keywords: Herbal therapies, Natural products, Euphorbia sp., Steroidal compounds, Biological activity, Amino acids, Fatty acids